Plant traits and litter decomposition of tree species naturally regenerating in Central America pasturelands - Esquivel Sheik, María J. (2013)
This research uses three consecutive approaches to evaluate the links among morphological diversity and ecosystem processes of 65 tree species commonly found in Central American active pasturelands (AP) under conventional management practices. Firstly, we explore tree morphological diversity measuring 17 plant traits (PT) to describe the functional strategies (FS) of tree species in agricultural lands. Secondly, we explore tree responses to anthropogenic disturbances like conventional pasture management testing the relationships of tree morphological diversity with tree abundances and exploring their relative utility to predict tree natural regeneration capacity (CNR) in agricultural lands. Thirdly, we test whether tree species variability in litter quality, decomposition rates and nutrient releases was related with tree morphological diversity and tree abundances to explore the effects of tree characteristics on litter quality, decomposition rates and nutrient releases was related with tree morphological diversity and tree abundances to explore the effects of tree characteristics on litter decomposition. This approximation allows exploring for the first time the effects of tree variability on ecosysteMON processes in anthropogenic environments and the possible effects of actual management over today and future provision of ecosystem services (ES) such as soil fertility replenishment and nutrient cycling offered by trees outside the remnant tropical forests.